Optimalisasi Program Continuing Professional Development (CPD) Untuk Mendukung Peningkatan Kompetensi dan Karir Perawat RSI Surabaya - Muhadi Muhadi; Titin Wahyuni (Jurnal Keperawatan Muhammadiyah, 2020)
Nurses are an integral part of patient care and play an important role in improving the quality of care in the hospital. Nurses have a responsibility to ensure patient safety with reliable and guaranteed competence. Nurse competence must be maintained through continuous professional development. The purpose of this study was to map the level of participation, driving and inhibiting factors for the implementation of the Continuing Professional Development (CPD) program. This study used a cross-sectional study design with a quantitative descriptive approach. The study population was all RSI nurses with a total sample of 104 survey participants with purposive sampling technique. Data were collected using an online questionnaire through the google form application from June to September 2020. Data analysis was carried out through SPPS 17 and presented in descriptive and tabulated narrative. The results of the study were the level of participation of nurses at the Surabaya Islamic Hospital in carrying out CPD activities which were divided into 3 categories, namely high, medium and low participation. A total of (17.3%) belonged to the low level of participation, (69.2%) the level of participation was medium and (13.5%) was classified as high. Some of the nurses in this survey reported reaching structural and clinical positions of nurses quickly through the skills, approaches and recommendations of managers. Short-term development plans are a priority for nurses' thinking in improving (CPD), namely the continuous fulfillment of complete nursing care practices and increasing the clinical career level. The long-term development plan for nurses is that some want to continue educational programs at a higher level such as specialized education and master's degree in nursing.